Examining older adults’ vulnerability to online health scams: insights from routine activity theory - Chen, Hongliang; He, Miao; Xu, Xiaowen; Atkin, David (Frontiers in Public Health, 2025)
IntroductionOnline health fraud has emerged as a significant digital risk for older adults in China, leading to considerable financial losses. This study aims to investigate the mechanisms underlying health fraud targeting and victimization among older adult populations, refining Routine Activity Theory (RAT) to account for the distinct stages of fraud exposure and victimization.MethodsA survey was conducted among retired individuals in July 2022. After removing incomplete responses, the final sample consisted of 471 participants. The survey assessed digital behavior patterns, exposure to promotional messages, health conditions, and fraud-related experiences.ResultsThe findings revealed that older adults who installed numerous mobile applications, frequently used social networking sites, and engaged in risky online behaviors were more likely to be targeted by health fraud. Additionally, exposure to promotional messages—both online and offline—and the presence of chronic diseases were significantly associated with increased fraud exposure. Regarding victimization, younger family intervention was found to mitigate financial losses, whereas older adults with limited digital protection skills experienced a higher likelihood of falling victim after exposure.DiscussionThis study refines the Routine Activity Theory by conceptualizing online health fraud as a two-stage process: exposure and victimization. The results highlight both digital behavior and offline contextual factors in shaping fraud vulnerability among older adults. The findings contribute to the theoretical understanding of cybercrime targeting the older adult and offer practical insights for designing preventive interventions tailored to this vulnerable population.